Effects of modified hybrid resistance training on dynamic control ratio of knee joint in untrained healthy subjects - Priyantono, Wirawan Indra; Tinduh, Damayanti; Sulistiawati, Nuniek Nugraheni; Melaniani, Soenarnatalina (Bali medical journal, 2023)
Background: Increased physical inactivity due to the COVID-19 pandemic has the potential to cause leg muscle strength decline due to the decrease in muscle mechanical loading. The hybrid training method uses the force generated by an electrically stimulated antagonist muscle to provide resistance to a voluntarily contracting agonist muscle. This exercise might be an effective choice for strengthening exercises during a pandemic because it does not require external resistance or stabilization devices. In addition, engaging the eccentric contraction of the antagonist muscle while the agonist is contracting concentrically may reduce agonist-antagonist muscle imbalance and reduce the risk of injury. Because the hybrid training system device was difficult to replicate, modifications were carried out using conventional stimulation tools. Methods: The research was conducted at the Medical Rehabilitation Installation of Dr. Soetomo General Academic Hospital Surabaya. The research subjects were 24 untrained healthy men aged 18-40 years divided into two groups: the treatment group who received modified hybrid strengthening exercises and the control group who received Russian protocol neuromuscular electrical stimulation (Russian NMES), 3 times per week for 4 weeks. Statistical tests were carried out on 12 treatment group subjects and 12 control group subjects who were able to complete the study. Results: There was a decrease in non-dominant 60o/sec DCR (p-value 0.002) and non-dominant 120o/sec DCR (p-value 0.019) in the treatment group. There was no significant difference in 60o/sec and 120o/sec DCR on both sides of the leg in the control group. There is a significant difference in ΔDCR between the two groups at non-dominant DCR 120o/sec (p-value 0.036). Conclusion: There was a greater reduction of knee joint DCR in the modified hybrid resistance training compared to the Russian NMES in untrained healthy subjects.